Intra- and inter-temporal effort allocation and profit-maximizing strategy of trawl fishery - Alizadeh, Tannaz; Abe, Keita (ICES Journal of Marine Science, 2021)
Bottom trawlers are engaged in multi-species fisheries and fish for profit. In quota-regulated fisheries, intra- and inter-temporal substitutions of fishing effort is regarded as a key mechanisms that influences the profitability of the fishing portfolio. The feeding and spawning migration patterns of the available fish species in the fishing portfolio alter the bio-economic conditions of the different fishing areas. In addition, the spatial heterogeneity among different fishing areas in terms of the fuel costs and travel distance, accessibility to other fishing fleets, and sea ice extent affects the relative attractiveness of the fishing areas and further complicates the decisions underlying the effort allocation, such as when and where to fish what and how much to fish to maximize the profit. In this regard, the aim of this article is to identify the key drivers of intra- and inter-temporal effort allocation in a multi-species trawl fishery consisting of 61 Norwegian trawl vessels targeting cod, saithe, and haddock, the aim being to maximize the fishing profit within the quota constraints. We adopted a two-step Heckman estimator that incorporates the relative attractiveness of three heavily trawled areas, the southern and northern parts of the west coast of Norway and the high sea areas of the Arctic. The relative attractiveness is specified by the fish availability, measured using the catch per unit of effort, prices of the target species, fuel cost, intensity of the coastal fleet's participation in winter fishery, and seasonal sea ice extent in the Barents Sea during the period 2011–2016. Our results show that region-specific attributes and spatial margins have a profound impact on the intra-temporal and inter-temporal allocation of fishing effort to maximize the seasonal profit. Furthermore, we found evidence of economically rational behaviour of the Norwegian trawlers in constantly reallocating their fishing effort in response to the changes in the relative attractiveness of the selected fishing areas over ...